1995
DOI: 10.1111/j.2042-3306.1995.tb04955.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of diet on weight and plasma variables in endurance exercised horses

Abstract: Summary The purpose of this study was to determine whether a difference in roughage intake could affect electrolyte and water balance in horses during endurance type exercise. In each of 2 experiments, 2 treatments (a high hay or limited hay diet) were assigned in a crossover design so that each horse performed 2 exercise tests, 1 on each treatment. In experiment 1, diet was controlled only the night before the exercise test. Water intake was lower (P<0.001) when horses received the limited hay diet. Exercise … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 10 publications
(5 reference statements)
3
12
0
Order By: Relevance
“…This could be beneficial for the prerace fluid balance of the horse. These findings also agree with TPP measured during exercise that showed higher TPP during exercise in horses fed a ∼50/50 hay/grain diet compared to horses fed a diet that contained more hay (Danielsen et al . 1995).…”
Section: Discussionsupporting
confidence: 89%
“…This could be beneficial for the prerace fluid balance of the horse. These findings also agree with TPP measured during exercise that showed higher TPP during exercise in horses fed a ∼50/50 hay/grain diet compared to horses fed a diet that contained more hay (Danielsen et al . 1995).…”
Section: Discussionsupporting
confidence: 89%
“…The change in TPP with altered fibre intake could therefore reflect changes in the equilibrium between the gut and the extracellular fluid. It has been shown that increased forage intake lowers TPP (Danielsen et al, 1995) and also that signs of dehydration (increased TPP) following feed deprivation are delayed in horses on a forage-only diet compared with those on a mixed diet . However, BW recovery was similar on both diets in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Similar effects have also been noted in cattle (Ramazin et al 1994). While these effects have not been studied in horses, it has been found that increasing hay intake causes corresponding increases in water intake (Meyer 1987;Danielsen et al 1995). In turn, this may lead to increased water in the gastrointestinal tract of horses with a concomitant increase in bwt.…”
Section: Introductionmentioning
confidence: 99%